PERANAN HUKUM ADAT DALAM PEMBANGUNAN DAN PEMBENTUKAN KITAB UNDANG-UNDANG HUKUM PIDANA NASIONAL - Ratna Winahyu Lestari Dewi (Perspektif, 2005)
Concept of Device of Criminal Code National (RKUHPNAS) have been compiled by since year 1972. But hitherto our state still go into effect the governmental KUHP heritage of Dutch colonial. in KUHP National which we dream of this, see that compiler team wish to strengthen the role of customary law in development and forming punish the national. This matter is seen in additional crime fallout. Conception the RKUHPNAS mention the respective sanction with the custom obligation. And so it is with coalescence of crime target which one of them is sliver related/relevant with the customary law existence.